Treatment of extended comminuted mandibular fractures with infected cutaneous fistule Post-ORIF using a reconstruction plate: A case report - Vityadewi, Nurardhilah; Prawoto, Almas Nur; Seswandhana, Muhammad Rosadi; Wahdini, Siti Isya; Ramli, Rianto Noviady; Dachlan, Ishandono (Elsevier BV, 2022)
Introduction: We report a case of an extended comminuted mandibular fracture using a reconstruction plate, miniplates and arch bar. Cases of extended comminuted mandibular fractures report high rates of complications. In this case, the patient subsequently suffered from an infected cutaneous fistule and non-union of the comminuted segments.